THE COMMUNICATIVE CRITERIA FOUND IN 10TH YEAR OF PUBLIC SENIOR HIGH SCHOOL ENGLISH COURSEBOOKS - Jessica Gunawan; Julia Eka Rini (Kata Kita: Journal of Language, Literature, and Teaching, 2016)
This thesis is a materials evaluation using communicative criteria. This topic is chosen considering that coursebooks are important teaching tools and communication ability is now a standard in pedagogical field. It aims to find the communicative criteria applied in the coursebooks. The writer attempts to find the criteria application and finds that the materials in the coursebooks apply to some extent the communicative criteria concerning the language knowledge, interaction, and language practice and use. The materials in the coursebooks are analyzed with constructed communicative criteria from Communicative Language Teaching principles by Larsen-Freeman and Anderson (2011). This study method is qualitative. The data are taken from English coursebooks for 10th Year of Public Senior High Schools in Indonesia. In conclusion, the coursebooks are fairly communicative because most materials apply one or more communicative criteria, except for materials in Vocabulary and Pronunciation sections. Further studies can be conducted on the materials suitability with students’ needs, the language skills and components and communicative competence taught.